#### Answer

f(x)=$\frac{x+8}{2x-1}$
f(-1)=$\frac{-1+8}{2(-1)-1}$
f(-1)=-$\frac{7}{3}$

#### Work Step by Step

f(x)=$\frac{x+8}{2x-1}$
f(-1)=$\frac{-1+8}{2(-1)-1}$
f(-1)=$\frac{7}{-3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

f(x)=$\frac{x+8}{2x-1}$
f(-1)=$\frac{-1+8}{2(-1)-1}$
f(-1)=-$\frac{7}{3}$

f(x)=$\frac{x+8}{2x-1}$
f(-1)=$\frac{-1+8}{2(-1)-1}$
f(-1)=$\frac{7}{-3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.